Effect of individualized positive end-expiratory pressure based on electrical impedance tomography guidance on pulmonary ventilation distribution in patients who receive abdominal thermal perfusion chemotherapy - Xiao, Li; Yu, Kang; Yang, Jiao-Jiao; Liu, Wen-Tao; Liu, Lei; Miao, Hui-Hui; Li, Tian-Zuo (Frontiers in Medicine, 2023)
Background Electrical impedance tomography (EIT) has been shown to be useful in guiding individual positive end-expiratory pressure titration for patients with mechanical ventilation. However, the appropriate positive end-expiratory pressure (PEEP) level and whether the individualized PEEP needs to be adjusted during long-term surgery (>6 h) were unknown. Meanwhile, the effect of individualized PEEP on the distribution of pulmonary ventilation in patients who receive abdominal thermoperfusion chemotherapy is unknown. The primary aim of this study was to observe the effect of EIT-guided PEEP on the distribution of pulmonary ventilation in patients undergoing cytoreductive surgery (CRS) combined with hot intraperitoneal chemotherapy (HIPEC). The secondary aim was to analyze their effect on postoperative pulmonary complications. Methods A total of 48 patients were recruited and randomly divided into two groups, with 24 patients in each group. For the control group (group A), PEEP was set at 5 cm H2O, while in the EIT group (group B), individual PEEP was titrated and adjusted every 2 h with EIT guidance. Ventilation distribution, respiratory/circulation parameters, and PPC incidence were compared between the two groups. Results The average individualized PEEP was 10.3 ± 1.5 cm H2O, 10.2 ± 1.6 cm H2O, 10.1 ± 1.8 cm H2O, and 9.7 ± 2.1 cm H2O at 5 min, 2 h, 4 h, and 6 h after tracheal intubation during CRS + HIPEC. Individualized PEEP was correlated with ventilation distribution in the regions of interest (ROI) 1 and ROI 3 at 4 h mechanical ventilation and ROI 1 at 6 h mechanical ventilation. The ventilation distribution under individualized PEEP was back-shifted for 6 h but moved to the control group’s ventral side under PEEP 5 cm H2O. The respiratory and circulatory function indicators were both acceptable either under individualized PEEP or PEEP 5 cm H2O. The incidence of total PPCs was significantly lower under individualized PEEP (66.7%) than PEEP 5 cm H2O (37.5%) for patients with CRS + HIPEC. Conclusion The appropriate individualized PEEP was stable at approximately 10 cm H2O during 6 h for patients with CRS + HIPEC, along with better ventilation distribution and a lower total PPC incidence than the fixed PEEP of 5 cm H2O. Clinical trial registration: identifier ChiCTR1900023897.